David Slater: a leading geographical theorist. Issue 2 (July 2020) - O'Keefe, Phil
David Slater is an enigmatic figure in radical geography. He is much regarded for his theoretical contributions to geography although few geographers seem to know to what he contributed. David Slater appeared on the radical geography scene in Dar es Salaam, Tanzania. Dar es Salaam was described, in the early 1970s, as being a 'hotspot' for radical geographers. He focused his work on a critique of modernisation theory, publishing a two-piece article in Antipode . He rejected the western notions of the working class as the pivot for revolutionary change and, instead, sought to explore the power of peasant-worker movements drawing particularly on his Latin American experience. He moved to Amsterdam, The Netherlands, where his work was increasingly anti-imperialist and focused on theoretical discussions of territoriality. He began to take more open post-colonial positions although he was wary of the cultural turn in geography. This wariness came from his observation that most Anglo-American geographers do field work in developing countries without the relevant local language. This, plus his demand for close readings of classic texts, including Marx, was admired, but little followed, by geographers. He sought to define territoriality as a kind of Third Space but Soja had already done this. He moved again to Loughborough, United Kingdom, where his work became more stridently anti-American and where his exploration of territoriality took him away from political geography to international relations, away from economics and history towards politics and political action. Latin American exile groups that he championed very fondly remember him in the United Kingdom. To the end, he continued to explore theories of social change. His demand for knowledge of language, local culture and classic texts made him a somewhat foreboding supervisor. The body of literature, particularly the early critiques of development theory, stand the test of time.